Scientific approaches to the study of migration - Dzhansarayeva R.Ye. (Хабаршы. Заң сериясы, 2016)
The article analyzes the scientific approaches to the study of migration. Migration – a complex and multidimensional phenomenon. This makes studying it in terms interdisciplinary approach to display the breadth of the spectrum of its nature and essence. In the study of migration are the following approaches: economic, demographic, migration, sociological, political, systemic, geographical, environmental, historical, ethnographic, psychological, biological, genetic, philosophical, legal, typological. The choice of approach depends on the problems that confront the researcher.